Sociodemographic inequalities in cardiovascular risk factors among adolescents from indigenous areas in Chiapas, Mexico - Elena Flores-Guillén; Itandehui Castro-Quezada; César Antonio Irecta-Nájera; Pilar E. Núñez-Ortega; Roberto Solís-Hernández; Rosario García-Miranda; Paola Cruz-Cruz; Christian Medina-Gómez; Xariss M. Sánchez-Chino; Zendy Evelyn Olivo-Vidal; Miguel Cruz; Héctor Ochoa- (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: This study was aimed to determine the prevalence of cardiovascular risk factors among different sociodemographic groups of adolescents from indigenous communities in Chiapas, Mexico. A cross-sectional prevalence study was performed in urban and rural communities in the Tzotzil-Tzeltal and Selva regions of Chiapas. A sample of 253 adolescents was studied, of whom 48% were girls and 52% were boys. A descriptive analysis of quantitative variables was performed using measures of central tendency and dispersion. The prevalence of cardiovascular risk factors stratified by sex, geographical area, years of schooling, and ethnicity of the mothers was estimated. The prevalence of cardiovascular risk factors was analyzed in relation to the sociodemographic characteristics of the study population. Low HDL-c (51%) was the predominant cardiovascular risk factor. Girls had a higher prevalence of abdominal obesity, hypertriglyceridemia, and borderline total cholesterol than boys. High diastolic blood pressure was more prevalent in boys. Adolescents from urban areas had a higher prevalence of overweight/obesity and insulin resistance than adolescents from rural areas. The prevalence of overweight/obesity and abdominal obesity was higher in adolescents whose mothers had ≥ 7 years of schooling compared with adolescents with less educated mothers. Differences by maternal ethnicity also influenced the prevalence of insulin resistance. Among the main findings, this study associated sociodemographic and geographical inequalities with cardiovascular risk factors. Promoting a healthy lifestyle for this young population is absolutely necessary to prevent cardiovascular diseases in adulthood.